IJCM_264A: An assessment of Dialysis services in the state of Chhattisgarh - Nanda Sarthak; Verma Nirmal; Jain Kamlesh (Wolters Kluwer Medknow Publications, 2024)
Background: In India, about 3.4 crore people need dialysis, with 2.2 million new cases of renal diseases every year. With approximately 4950 dialysis centres, the demand is less than half met. Every Dialysis has an additional expenditure tag of about Rs.2000, it results in expenditure of Rs.3-4 Lakhs annually for the patient. The Dialysis Program under Public Private Partnership was formally announced in the Union Budget 2016-17 by the Honourable Finance Minister. Objective: To assess the dialysis centres working under the National Dialysis Programme. To look at the resources and equipment's of various centres to look at the patient load of various centres Methodology: The teams from Pt. J.N.M Medical college went to 8 centres of various centres giving dialysis services. This covered 75% of the centres of the state. Centre staff as well as patients were interviewed. The interview was conducted using a predesigned, validated, semi-structured questionnaire. Results: The staff working in the centres is well trained and they are managing the workload well. The technicians are doing well in terms of giving services and most of the centres have multiple machines. Raipur is the most advanced one. Conclusion: These dialysis centres are doing a good job in managing workload however, the centres should have a dedicated Medical officer for the centre. Although, workload is well managed because of Medical Officers working in DH and trained staff of the centre, the medical officers of District Hospital can be trained for reduction of employment stress